Rickettsial infections in ticks from reptiles, birds and humans in Honduras - Novakova, Marketa; Literak, Ivan; Chevez, Luis; Martins, Thiago F; Ogrzewalska, Maria; Labruna, Marcelo B (Ticks and tick-borne diseases, 2015)
Ticks were collected from captive reptiles, wild birds, and incidentally from humans at two locations in Honduras and part of these were tested for the presence of Rickettsia using polymerase chain reaction. The following species of ticks were found: Amblyomma dissimile on Iguanidae reptiles, Amblyomma longirostre and Amblyomma nodosum on birds, and Amblyomma mixtum (Amblyomma cajennense complex) on humans. A. dissimile was infected with Rickettsia sp. strain Colombianensi. Both A. longirostre and A. mixtum were infected with Candidatus 'Rickettsia amblyommii'. This study provides the first report of rickettsial infections in ticks from reptiles, birds and humans in Honduras. New host - Amblyomma tick associations are documented.
Keywords: Animals; Rickettsia; Birds; Female; Honduras; infestace klíšťaty; ženské pohlaví; nymfa; lidé; Molecular Sequence Data; nemoci ptáků; Amblyomma; ptáci; Nymph; Bird Diseases; klíšťata; molekulární sekvence - údaje; Ticks; Male; Lizards; interakce hostitele a patogenu; ještěři; Larva; zvířata; mužské pohlaví; Host-Pathogen Interactions; Tick Infestations; Reptiles; larva; Humans